The Effect of Flexible Working Arrangement on Organizational Commitment - Lathiefa Nur Ilma; Devid Efraim Dinar; Evelyn Hendriana (Budapest International Research and Critics University, 2022)
In early 2020, the Coronavirus (COVID-19) spread and had many impacts on various sectors throughout the world, including in the economic and social fields. This then also affects how companies adapt to current work methods. One of the significant changes as a result of COVID-19 is the increasing number of companies adopting flexible work arrangements (Kramer & Kramer, 2020). On the other hand, flexible work arrangements also increase the pressure on the balance of work and domestic work (Kazekami, 2020). In many developing countries, many employees are suddenly forced to telecommute because of the pandemic. As a result, they need to make some adjustments that can have an impact on their performance, satisfaction, and loyalty to the company. The aims of this study were: first to examine the effect of work flexibility on work-family conflict and mental health, especially on job stress; the second investigates whether work-family conflict and job stress mediate between job flexibility and employee job satisfaction; and third, to investigate whether work flexibility has a role on employee organizational commitment mediated by work-family conflict, job stress, and job satisfaction. This research is descriptive to describe the characteristics and phenomena studied. The research was conducted using a survey method using a research instrument in the form of a questionnaire with a Likert scale weighting. This study produces new information that explains the relationship structure of the relationship between job flexibility and employee commitment to the company. The results of this study indicate that commitment to the company is directly influenced by job satisfaction. Then not only job satisfaction, a person's stress level at work also has an influence on one's commitment, this is indicated by the influence that involves mediating one's work satisfaction.